A study on the effect of aspirin on clinical symptoms, laboratory indices, and outcomes in patients with COVID-19 - Roham Azizi; Maryam Dehghani Mobarakeh; Reza Goujani; Mohsen Nabi-Afjadi; Soheil Mousavi Rizi; Ahmadreza Maghsoudi (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: Low-dose aspirin is one of the most widely used secondary prevention agents for cardiovascular disease and stroke. An unstable risk factor for chronic cardiovascular disease is a viral infection. Evidence suggests that the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could increase the risk of acute cardiovascular events by inducing systemic inflammatory responses and instability in coronary plaques. Objectives: The present study aimed to examine the impact of aspirin on clinical symptoms, laboratory indices, and clinical outcomes in patients with COVID-19. Patients and Methods: After reviewing the documents of hospitalized patients at the Dr. Shariati hospital in Isfahan, Iran, while case and control groups were selected using a cross-sectional method based on aspirin use and non-use. Following a random selection of the reference population (131 medical records of patients with COVID-19 who had aspirin use and 131 of the group of patients with COVID-19 without aspirin use). Medical records of patients with cardiovascular disease, diabetes, cardiovascular disease with diabetes, and patients without underlying disease were evaluated. After matching the two groups based on age, gender, and medical history, the examination and results were recorded in a questionnaire. Results: The results showed that during treatment, no significant difference between the case and control groups regarding clinical symptoms, laboratory results, the need for bilevel positive airway pressure (BiPAP), and mechanical ventilation (P=0.0111 and P=0.089, respectively) were observed. Moreover, no significant difference in the outcome, including improvement and death was detected (P=0.962). Likewise, no significant difference in hospitalization duration between the aspirin and control groups was seen (P=0.289). Conclusion: Our study on a group of COVID-19 patients showed, aspirin is ineffective on clinical symptoms, laboratory indices, and outcomes, however our results further investigation by multi-centric investigations.